Trends and Clinical Outcomes of In Vitro Fertilization in Selected Nigerian Cities: A Multi-Center Retrospective Study - Swesme, Enyioma-Alozie (Innovation in Science and Technology, 2025)
Background: The advent of In vitro fertilization (IVF) in the late 20th century has greatly transformed reproductive medicine. It has brought hope to millions of individuals and couples facing the challenges of infertility. Assisted Reproductive Technology (ART), notably In Vitro Fertilization (IVF), has shown promise in treating infertility, yet its use in Nigeria is limited by high costs, inconsistent success rates, and a lack of standardized clinical protocols. Aim: The current study investigated the trends and clinical outcomes of IVF treatments in two Nigerian cities, Abuja and Jos, between 2016 and 2022, providing a comprehensive analysis of IVF demand, success rates, and associated risk factors. Methodology: A retrospective analysis of 26,233 medical records from four fertility centers in Abuja and Jos was conducted. Data, including clinical indications, treatment outcomes, and infertility-related variables, were extracted from patient records spanning six years. Descriptive statistics and comparative analyses were employed to examine trends and identify significant factors affecting IVF success. Results: The study revealed a notable increase in IVF cases, with Abuja Hospital showing a surge from 503 cases in 2018 to 1,665 in 2022. Success rates varied, with Abuja Hospital achieving a 94% success rate in 2021. Male infertility was a primary cause of IVF failure, and multiple pregnancies were common, especially in 2022, with 974 multiple pregnancies out of 1,552 successful IVF treatments at Abuja North Hospital. Conclusion: The findings demonstrate growing demand for IVF services in Nigeria, with a high incidence of multiple pregnancies. These trends highlight the need for improved embryo selection and management protocols. This study provides valuable insights for optimizing IVF practices and improving patient outcomes in Nigeria.